2003
DOI: 10.1002/cne.11004
|View full text |Cite
|
Sign up to set email alerts
|

Unique expression patterns of 5‐HT2A and 5‐HT2C receptors in the rat brain during postnatal development: Western blot and immunohistochemical analyses

Abstract: Serotonin (5-HT) is recognized as a potential regulatory factor in neuronal development. Two subtypes of receptors for it, 5-HT2A and 5-HT2C, are distributed broadly in the rat brain, suggesting their role in a variety of brain functions. Here, we investigated the expression patterns of these 5-HT2 receptors in the rat brain during postnatal development by using Western blot and immunohistochemical analyses. By Western blot analysis, the expression of the 5-HT2A receptor was at a low level at postnatal day 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 55 publications
4
59
0
Order By: Relevance
“…Among thalamic 5-HTRs (Mengod et al 2010), 5-HT 1A Rs and 5-HT 2A Rs, which are coupled to Gαq/G11-proteins and activate phospholipase C (PLC) β (Di Giovanni et al 2006), are relatively highly expressed in the GABAergic neurons of the NRT (Li et al 2004;Bonnin et al 2006;Rodriguez et al 2011). 5-HT 1A Rs are mainly present on the soma and proximal dendrites of these neurons, whereas 5-HT 2A R are less abundant and moderately expressed on cell bodies and more abundant on fine and medium-sized dendrite (Rodriguez et al 2011).…”
Section: Thalamusmentioning
confidence: 99%
“…Among thalamic 5-HTRs (Mengod et al 2010), 5-HT 1A Rs and 5-HT 2A Rs, which are coupled to Gαq/G11-proteins and activate phospholipase C (PLC) β (Di Giovanni et al 2006), are relatively highly expressed in the GABAergic neurons of the NRT (Li et al 2004;Bonnin et al 2006;Rodriguez et al 2011). 5-HT 1A Rs are mainly present on the soma and proximal dendrites of these neurons, whereas 5-HT 2A R are less abundant and moderately expressed on cell bodies and more abundant on fine and medium-sized dendrite (Rodriguez et al 2011).…”
Section: Thalamusmentioning
confidence: 99%
“…In fact, 5-HT 2 receptors are major targets for a wide array of psychoactive drugs, ranging from non-classical antipsychotic drugs, anxiolytics and anti-depressants, which have a 5-HT 2 antagonistic action, to hallucinogens, which are agonists of the 5-HT 2 receptors [34][35][36][37]. Furthermore, recently it has been shown that 5-HT 2 receptors have a potential significance in brain development [38], and in experiencedependent plasticity in the visual cortex [39]. The 5-HT 2 receptor form a closely related subgroup of G-proteincoupled receptors and show the typical heptahelical structure of an integral membrane protein monomer.…”
Section: -Ht 2 Familymentioning
confidence: 99%
“…This may relate to the inadequacy of techniques to determine the receptor in tissue samples. However, evidence from a variety of sources has involved this receptor in several important physiological and psychological processes including motor function, anxiety, ingestive behaviour and in brain development [33,38,[65][66][67]. 5-HT 2C receptor-deficient mice are overweight as a result of abnormal control of feeding behaviour [68,69], thus this receptor could play a role in the serotonergic control of appetite.…”
Section: -Ht 2c Receptorsmentioning
confidence: 99%
“…7) Moreover, it has been reported that the 5-HT2CR is not only involved in signal transduction, but also plays an important role in neuronal development. 2,12) We have demonstrated that blockade of 5-HT2CR by imipramine up-regulated 5-HT2C mRNA expression level and suppressed cell growth in a NG108-15 cell line. 13) Together, these findings allow us to infer that the 5-HT2CRs, probably some isomers, may be synthesized in the brain and contribute to neuronal growth and/or neuronal development.…”
mentioning
confidence: 90%
“…[1][2][3] Messenger RNA of 5-HT2CR, as well as some other genes such as a-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) type glutamate receptor mRNA 4) and GABA A receptor a3 subunit mRNA, 5) undergoes adenosine-to-inosine (A-to-I) RNA editing 6) in their cording regions which are mediated by adenosine deaminases (ADARs). Burns et al 6) have identified five editing sites (named A, B, E (CЈ), C and D from the 5Ј-side) located in the 5-HT2C mRNA sequence encoding the second intracellular loop domain of 5-HT2CR (Fig.…”
mentioning
confidence: 99%